Analisis Bibliometrik Tren Penelitian Media Sosial Pemerintah Daerah di Indonesia (2014-2024) - Laksana, Muhibudin Wijaya; Satria, Iqbal Reza; Renata, Mira (Jurnal Ilmu Politik dan Pemerintahan, 2025)
This study aims to map trends and identify research gaps on local government social media in Indonesia in the period 2014–2024. The method used is bibliometric analysis with data obtained from the GARUDA database. The analysis was carried out using Microsoft Excel and VOSviewer to examine the frequency, relevance, and density of themes based on 87 selected articles. The results of the study show that studies on local government social media have increased significantly since 2020, dominated by qualitative approaches and focused on the Instagram platform. There are gaps in terms of diversification of approaches, new platforms, and regional objects studied. These findings provide a basis for developing further research that is more contextual and diverse.